Manufacturing System Lean Improvement Design Using Discrete Event Simulation - Salonitis, Konstantinos; Omogbai, Oleghe (Elsevier, 2017)
Lean manufacturing (LM) has been used widely in the past for the continuous improvement of existing production systems. A Lean Assessment Tool (LAT) is used for assessing the overall performance of lean practices within a system, while a Discrete Event Simulation (DES) can be used for the optimization of such systems operations. Lean improvements are typically suggested after a LAT has been deployed, but validation of such improvements is rarely carried out. In the present article a methodology is presented that uses DES to model lean practices within a manufacturing system. Lean improvement scenarios are then be simulated and investigated prior to implementation, thereby enabling a systematic design of lean improvements.
Keywords: Lean manufacturing; lean assessment; discrete event simulation